Negara Religius: Konsep Wilâyat Al-Faqîh Imam Khomeini dalam Sistem Kenegaraan Iran - Bisri, H.Hasan (Research and Development Institution, Darussalam Institute for Islamic Studies, 2017)
The discourse of the relationship between religion and state, which is sometimes more known as politic, has become a topic of interest in human life. The discussion resulted generally in three different group of thought. The first is contra group, those who obviously refuse the influence of religion towards state; the second is just the opposite, they apparently affirm that there is a strong and tight relationship between religion and state; and the last is middle group that try to compromise the two contradictive ideas. This study investigates the form of relationship between religion and state as reconciliation between religion authority on one hand and people authority on the other through the implementation of Khomeini's innovative idea of wilayat al-faqih in the constitution of Islamic Republic of Iran; and the models of democracy implemented in developing and conducting the governance of the country.